Information Technology in Logistics: Advantages, Challenges and Opportunity for Efficiency from Problem Decision in Diferent Activities - Krstev, Aleksandar; Donev, Aleksandar; Krstev, Dejan (Natural Resources and Technology, 2013)
Informatisation, internationalisation and globalisation have dramaticallychanged retail sector; speeding up the retail processes, creating new saleformats, fastening the increase of income etc. During the last decade, logisticsinfl uenced the development of retailing by cutting down costs and increasing theservice quality level. The main purpose of this paper is to give a comprehensivereview of affected logistics and directly caused changes in Western Balkanretailing and global market as well. Among the given trends there is a shorterproduct life cycle that induces some changes among supply chain members inorder to keep profi tability, innovation in technology fi eld, RFID technology,automated commercial processes, and EDI system communications.Based on the analysis of relevant foreign literature in the area of logistics,distribution and supply chain management, this paper gives a review of newmarket trends that have an important impact on logistics. Special attentionis given to more signifi cant usage of concept of managing, developing highquality products and services, minimising stock within supply chain andmaking sustainable, competitive and strategic advantage of a company by it.